2019
DOI: 10.1038/s41598-019-43145-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved contrast of affibody-mediated imaging of HER3 expression in mouse xenograft model through co-injection of a trivalent affibody for in vivo blocking of hepatic uptake

Abstract: Human epidermal growth factor receptor type 3 (HER3) plays a crucial role in the progression of many cancer types. In vivo radionuclide imaging could be a reliable method for repetitive detection of HER3-expression in tumors. The main challenge of HER3-imaging is the low expression in tumors together with endogenous receptor expression in normal tissues, particularly the liver. A HER3-targeting affibody molecule labeled with radiocobalt via a NOTA chelator [ 57 Co]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…than the bivalent variants 33A and 3A3 [24]. It has previously been shown that a trimeric anti-HER3 affibody (without an ABD) had a 10-fold higher hepatic uptake than a monomeric affibody, supposedly due to the slower dissociation of the multivalent affibody and HER3 sequestration [32]. It could be speculated that the bivalent therapeutic variants have a similar effect, and as a result, the hepatic uptake of 68 Ga-(HE) 3 -Z HER3 -NODAGA was observed in the 3A treated group, but not the 3A3 and 33A groups.…”
Section: Discussionmentioning
confidence: 96%
“…than the bivalent variants 33A and 3A3 [24]. It has previously been shown that a trimeric anti-HER3 affibody (without an ABD) had a 10-fold higher hepatic uptake than a monomeric affibody, supposedly due to the slower dissociation of the multivalent affibody and HER3 sequestration [32]. It could be speculated that the bivalent therapeutic variants have a similar effect, and as a result, the hepatic uptake of 68 Ga-(HE) 3 -Z HER3 -NODAGA was observed in the 3A treated group, but not the 3A3 and 33A groups.…”
Section: Discussionmentioning
confidence: 96%
“…This approach increased the tumor-to-liver ratio by ca. [41] in a BxPC-3 xenograft model. It has to be noted that although both EGFR and HER3 are expressed in normal tissues, including liver, the expression level of HER3 in tumors is appreciably lower than the level of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect radioiodination of (HE) 3 -Z HER3:08698 -DOTAGA using N-succinimidyl-para-(trimethylstannyl)benzoate was performed as described earlier for affibody molecules [49] and DARPins [48]. An aqueous solution of 0.1% acetic acid (60-90 µL) was added to radioiodine (40)(41)(42)(43)(44)(45). Then, N-succinimidyl-p-(trimethylstannyl)benzoate (6.5 nmoles, 2.5 µg, 2.5 µL of 1 mg/mL in 5% acetic acid in methanol) and chloramine-T (80 µg, 10 µL, 8 mg/mL in water) were added.…”
Section: Radiolabeling and Label Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Radiometals have their deserved place in the toolbox of nuclear medicine: cobalt ( 57 Co, 271.8 d; as a surrogate for 55 Co, 17.5 h) and indium ( 111 In, 2.8 d) were used as labels for affibody monomers targeting tumours in BxPC-3 xenografted mice 27 . A further contribution broaches the application of nanospheres labelled with 89 Zr (78.4 h) 28 , a positron emitter with a half-life roughly matching the in vivo circulation of antibodies.…”
Section: Collection Overviewmentioning
confidence: 99%